PRACTICAL ISSUES IN THE APPLICATION OF THE PROCEDURAL INSTITUTION OF PRELIMINARY COURT HEARINGS - Melkonyan, Davit (State and Law, 2025)
The new Criminal Procedure Code of the Republic of Armenia has introduced fundamental changes to the structure of proceedings in the court of first instance. The trial stage has been divided into three mandatory sub-stages: preliminary, main, and supplementary hearings, each having its own distinct procedural tasks. Preliminary hearings are considered a new, independent procedural institution, the purpose of which is to eliminate shortcomings made in the previous stages and to prepare the proceedings for the main hearings.During the preliminary hearings, the court examines a number of strictly defined issues, including the matter of preventive measures, as well as the scope and admissibility of evidence.In practice, however, the legal regulations regarding the issues subject to discussion during the preliminary hearings are applied inconsistently, which prevents the realization of the content originally intended in those regulations.The article highlights the most common violations encountered in legal practice and presents practical recommendations aimed at ensuring the purposeful application of the institution of preliminary hearings.
Keywords: Preliminary hearing; Criminal Procedure Code; Evidentiary scope; Judicial efficiency; Equality of arms; Adversarial principle; Preventive measures